Increasing dietary sodium chloride promotes urine dilution and decreases struvite and calcium oxalate relative supersaturation in healthy dogs and cats. Issue 5 (10th March 2020) - Queau, Yann; Bijsmans, Esther S.; Feugier, Alexandre; Biourge, Vincent C.
Abstract: Urolithiasis is highly prevalent in dogs and cats, with struvite and calcium oxalate being most commonly diagnosed. Some commercial diets aimed at reducing the risk of urolithiasis are based on inclusion of sodium chloride (NaCl) in an attempt to dilute the urine and the risk of crystallization, but more information on the effect of differing levels of sodium inclusion is needed. The objective of this study was to compare the short‐term effect of four diets differing only in NaCl content (base diet with 0.3% sodium and diets with added NaCl to achieve 0.7, 1.0 and 1.3% sodium as fed) on urinary ion concentrations and relative supersaturation (RSS) of struvite and calcium oxalate in dogs and cats. In both species, there was a significant increase in water intake and urine volume as dietary NaCl increased. Urine sodium concentration increased with increasing dietary NaCl. The highest sodium diet increased urinary calcium excretion in dogs only, while decreasing urinary calcium concentration. Calcium oxalate RSS and struvite RSS both significantly decreased, with the lowest RSS values reported on the highest sodium diet in both dogs and cats ( p  < .001). These results suggest that an increase in dietary NaCl decreases RSS values in both dogs and cats. Despite an increase in urinary calcium excretion in dogs, urinary calcium concentration and calcium oxalate RSS were lower on high sodium diets due to urine dilution. Long‐term studies are needed to confirm the relationship between RSS and stone occurrence and recurrence.